ANALISIS HARGA SAHAM PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Greydi Razzaq Toffano Widajanto (2021)
This research is using quantitative study aimed to see whether there are influence of profitability, solvability, inflation, and interest rate on the banking stock price. This study uses stock price in bank industry that listed in Indonesia Stock Exchange from 2017-2019. Saturated sampling is used in this study that used 39 listed bank in Indonesia. Testing the hypothesis in this study was used Multiple Linear Regression Analisys using E-Views 10 analysis tool. The result of this test indicate that (1)Profitability affect banking stock price,(2) Solvability not affect banking stock price, (3) Inflation not affect banking stock price, (4) Inflation not affect banking stock price